Association of concentrations of beta-carotene in plasma on pregnancy per artificial insemination and pregnancy loss in lactating Holstein cows - Madureira, A. M. L.; Pohler, K. G.; Guida, T. G. [UNESP]; Wagner, S. E.; Cerri, R. L. A.; Vasconcelos, J. L. M. [UNESP] (Elsevier B.V., 2020)
The objective of this study was to determine the association of beta-carotene concentration in plasma at the moment of artificial insemination (AI) on pregnancy/AI in lactating Holstein cows. A total of 399 events from 364 lactating Holstein cows were enrolled in the trial (143 primiparous and 221 multiparous). AIl cows were assigned to a timed AI protocol based on estradiol and progesterone. Blood samples were collected at the moment of AI and at 24 and 31d post-AI (samples on 31 d post-AI were collected only from cows that were diagnosed pregnant). The BCS were recorded at the time of AI. Plasma betacarotene was quantified from blood samples taken at the time of AI using a single step denaturation and extraction into a solvent, followed by measurement using a portable spectrophotometer. Pregnancy-associated glycoproteins (PAG) were analyzed in blood samples taken at 24 and 31 d post-AI of pregnant cows. Milk production was collected for the entire experimental period. Pregnancy diagnosis was performed by ultrasound 31 and 60 d post-AL Data was analyzed using the MIXED and GLIMMIX procedures of SAS. Cows classified as thin (<2.75) tended to have lower concentration of beta-carotene at AI when compared with those classified as Moderate (+/- 3.00; 3.8 +/- 0.1 vs. 4.3 +/- 0.1 mu g/mL; P= 0.09). Concentration of beta-carotene were greater in multiparous compared with primiparous (P< 0.01). There was no correlation between concentration of beta-carotene and milk production (r = 0.04; P=0.10). When plasma beta-carotene was categorized in quartiles, cows in the 1st quartile had lower pregnancy/AI and higher pregnancy losses when compared with cows that were in the 2nd, 3rd and 4th quartile (pregnancy/AI = 19.2 +/- 4.5, 33.7 +/- 4.7, 36.9 +/- 5.0 and 39.8 +/- 5.4%, respectively; P= 0.05; pregnancy losses = 41.9 +/- 4.8, 20.4 +/- 3.7, 22.1 +/- 4.1, and 15.7 +/- 4.2%, respectively; P<0.05). There was no association between concentrations of beta-carotene at AI and PAG at 24 d post-AI (P=0.60). Cows with greater concentrations of beta-carotene at AI were more likely to have greater concentrations of PAG at 31 d post-AI (P< 0.01). In conclusion, the concentration of beta-carotene at AI was affected by BCS and parity. Cows with higher concentrations of plasma beta-carotene at AI had greater pregnancy/AL lower pregnancy losses and greater concentrations of PAG at d 31 post-AI suggesting it may be associated with placental function in lactating dairy cows. (C) 2019 Elsevier Inc. AIl rights reserved.
Keywords: Pregnancy/AI; Beta-carotene; Pregnancy-associated-glycoprotein